Determination of the branching fractions of B0S→ D∓SK∓ and B0 → D-SK+ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Fontana, Marianna; et al. (Journal of high energy physics, 2015)
Measurements are presented of the branching fractions of the decays BS0→ DS∓K∓ and B0 → DS−K+ relative to the decays BS0→ DS−π+ and B0 → D−π+, respectively. The data used correspond to an integrated luminosity of 3.0 fb−1 of proton-proton collisions. The ratios of branching fractions areℬBs0→Ds∓K∓ℬBs0→Ds−π+=0.0752±0.0015±0.0019$$ \frac{\mathrm{\mathcal{B}}\left(B_{s}^0→ D_{s}^{\mp }{K}^{\mp}\right)}{\mathrm{\mathcal{B}}\left(B_{s}^0→ D_{s}^{-}{π}^{+}\right)}=0.0752± 0.0015± 0.0019
Im Titel sind die Zeichen "0", "∓", "+" und "-" hochgestellt
Im Titel ist Buchstabe "s" tiefgestellt
Gesehen am 07.10.2020
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, S. Wandernoth, D. Wiedner, A. Zhelezov [und 670 weitere]